2017
DOI: 10.1038/srep40423
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional surgical simulation improves the planning for correction of facial prognathism and asymmetry: A qualitative and quantitative study

Abstract: Traditional planning method for orthognathic surgery has limitations of cephalometric analysis, especially for patients with asymmetry. The aim of this study was to assess surgical plan modification after 3-demensional (3D) simulation. The procedures were to perform traditional surgical planning, construction of 3D model for the initial surgical plan (P1), 3D model of altered surgical plan after simulation (P2), comparison between P1 and P2 models, surgical execution, and postoperative validation using superim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 57 publications
2
80
0
Order By: Relevance
“…Previous comparative studies have shown that 3D simulation provides superior results for OGS treatment compared to 2D planning, with disparities between the studies for sample compositions, outcome measure tools, and endpoints of research 15,16,[28][29][30][31][32][37][38][39] . This study was designed to investigate possible differences of facial contour asymmetry after OGS treatment in a cohort of patients with clefts, depending on either 2D-or 3D-guided planning modality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous comparative studies have shown that 3D simulation provides superior results for OGS treatment compared to 2D planning, with disparities between the studies for sample compositions, outcome measure tools, and endpoints of research 15,16,[28][29][30][31][32][37][38][39] . This study was designed to investigate possible differences of facial contour asymmetry after OGS treatment in a cohort of patients with clefts, depending on either 2D-or 3D-guided planning modality.…”
Section: Discussionmentioning
confidence: 99%
“…Meticulous treatment of patients with combined abnormalities (such as clefts, malocclusion, and asymmetry) may require a precise mobilization of the maxillary and mandibular segments to address all possible deformities in a single procedure 15,16,26 . Based on the evolving experience of our center 15,16,26,30,45 , the single-splint two-jaw OGS approach provides enormous surgical flexibility for the treating surgeon, allowing the positioning of the maxillomandibular complex in six degrees of free movement with achievement of the desired position that yields the best balance between functional occlusion and facial esthetic and symmetric results. However, this multidirectional movements of maxillomandibular complex cannot be precisely anticipated by using the conventional 2D planning 21,22 .…”
Section: Lateral Lower Chin N (%)mentioning
confidence: 99%
See 3 more Smart Citations